1995
DOI: 10.1177/0011000095234011
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Coping with Cultural Diversity

Abstract: Coping with cultural diversity is one of the major challenges facing individuals who seek counseling services as well as those who provide those services. This article describes six strategies, (a) assimilation or monoculturation, (b) acculturation, (c) alternation, (d) integration, (e) separation, andf) fusion that individuals may use to cope with cultural diversity. The relationship between these strategies, an ecosystemic model of culture, and a social cognitive theory of behavior is presented. The article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…Coleman's (1995b) model hypothesized that the strategies would cluster together in a particular manner. He suggested that those strategies that involve association with only one culture would be strongly related to each other as would those that involved associating with more that one culture.…”
Section: Discussion and Implications For Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman's (1995b) model hypothesized that the strategies would cluster together in a particular manner. He suggested that those strategies that involve association with only one culture would be strongly related to each other as would those that involved associating with more that one culture.…”
Section: Discussion and Implications For Counselingmentioning
confidence: 99%
“…An individual can either score high, medium, or low in these categories (e.g., acculturated, bicultural, lowacculturated). Coleman (1995b) proposed an alternate paradigm for understanding how individuals manage the process of second culture acquisition. Coleman argued that traditional conceptualizations focused on the outcomes of the second culture acquisition.…”
mentioning
confidence: 99%
“…1993) have explored the effect of culture on the counseling process. The purpose of this article is to show how strategies counselors and clients use to cope with cultural diversity (Coleman, 1995b) can be a source of conflict and how theories of counseling and human development that are brought to the counseling relationship mler. Brome, &Williams, 199 1) can help to address and resolve conflict.…”
mentioning
confidence: 99%
“…I have described the aforementioned process in detail (Coleman, 1995b). The decisions involved are not mutually exclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation